The Interplay Between Gut Microbiota and miRNAs in Cardiovascular Diseases - Ionescu, Ruxandra Florentina; Enache, Robert Mihai; Cretoiu, Sanda Maria; Cretoiu, Dragos (Frontiers in Cardiovascular Medicine, 2022)
The human microbiota contains microorganisms found on the skin, mucosal surfaces and in other tissues. The major component, the gut microbiota, can be influenced by diet, genetics, and environmental factors. Any change in its composition results in pathophysiological changes that can further influence the evolution of different conditions, including cardiovascular diseases (CVDs). The microbiome is a complex ecosystem and can be considered the metagenome of the microbiota. MicroRNAs (miRNAs) are speculated to interact with the intestinal microbiota for modulating gene expressions of the host. miRNAs represent a category of small non-coding RNAs, consisting of approximately 22 nucleotides, which can regulate gene expression at post-transcriptional level, by influencing the degradation of mRNA and modifying protein amounts. miRNAs display a multitude of roles, being able to influence the pathogenesis and progression of various diseases. Circulating miRNAs are stable against degradation, due to their enclosure into extracellular vesicles (EVs). This review aims to assess the current knowledge of the possible interactions between gut microbiota, miRNAs, and CVDs. As more scientific research is conducted, it can be speculated that personalized patient care in the future may include the management of gut microbiota composition and the targeted treatment against certain expression of miRNAs.